Pengaruh Body Shaming Terhadap Kepercayaan Diri Mahasiswa Di Universitas Ali Sayyid Rahmatullah Tulungagung - Nella Rahmawati; Muhammad Sholihuddin Zuhdi (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2022)
This research is motivated by the many phenomena of verbal bullying that occur in the community. One of them is commenting on other people's physical or what is called body shaming. When a person enters the phase of adolescence, of course there will be changes in body shape, but sometimes the changes in body shape that occur are not in accordance with community standards and these changes carry over into adulthood. This study aims to determine and understand the effect of body shaming on student self-confidence. The data analysis technique refers to Clark Moustakas' phenomenology. The subject is a student who experiences body shaming. This research shows that body shaming treatment can happen to anyone, and this has an effect on students' low self-confidence.